PENDAMPINGAN PENGELOLAAN PERKEBUNAN DALAM MENINGKATKAN KUALITAS LINGKUNGAN DAN PEREKONOMIAN DI DESA JEMARAS KALIMANTAN TENGAH - Ahmadi Ahmadi; Yuliani Khalfiah, Noorhana Sesar Sari, Muhammad Arsat (Adiba Aisha Amira, 2022)
Indonesia is known as an agrarian country that relies heavily on the results of the agricultural and plantation sectors as a source of livelihood and as a support for development. One of the agricultural sub-sectors is plantation, which has a great opportunity to improve the people's economy in the development of the Indonesian economy. The phenomenon of smallholder plantations that are often found in the villages of Cempaga District, Kotawaringin Timur Regency, Central Kalimantan, especially in Jemaras Village, makes the surrounding environment not of good quality, due to the large amount of plantation waste that is disposed of on the riverbanks of the village. In addition, plantation waste has not been utilized optimally so that it has no economic value. The plantation management assistance program for the Jemaras Village community received a fairly good response, which was carried out using limited face-to-face technical methods. Community activities towards plantation waste management as well as awareness of the quality of environmental hygiene are getting better. The achievements shown in the final stage illustrate the success of the mentoring program with high public awareness to utilize palm leaf waste into a productive commodity. In addition to increasing the quality of good plantation management, negative impacts such as environmental damage can be mitigated as much as possible.